Heteropolycompounds as catalysts for biomass product transformations - Sanchez, Laura Mabel (2016)
In this article we show a variety of biomass product transformations through catalysis by both bulk and supported heteropolycompounds. The biomass sources considered include carbohydrates, oils and fats, and terpenes as main starting material groups. The products obtained and their applications are presented.